Adherence to vaccination against SARS-CoV-2 and vaccine safety in patients with IgG4-related disease - Mastromanno, Linda; Giardina, Federico; Gattamelata, Angelica; Colafrancesco, Serena; Truglia, Simona; Spinelli, Francesca Romana; Simoncelli, Edoardo; Lucchino, Bruno; Conti, Fabrizio; Priori, Roberta (Reumatismo, 2025)
Objective. To assess the adherence to the vaccination campaign against SARS-CoV-2 in patients with IgG4-related disease (IgG4-RD) and to evaluate the development of local and systemic adverse events (AEs) following vaccination. Additionally, to investigate the rate and outcome of SARS-CoV-2 infection in IgG4-RD patients.Methods. Patients with IgG4-RD in follow-up before the onset of the SARS-CoV-2 pandemic were contacted by telephone and asked to answer an ad hoc questionnaire regarding their vaccination status against SARS-CoV-2 and related AEs following vaccination. The occurrence and the outcome of SARS-CoV-2 infection were also recorded. The same questionnaire was proposed to healthy controls (HC).Results. 20 patients and 40 HC were enrolled. In the patient’s cohort, 90% were vaccinated with at least one dose; among them, 11 reported AEs: 61.1% systemic and 22.2% local. Within the HC group, 100% were vaccinated with at least one dose. 20 out of 40 HC had systemic AEs (50%), and 27 (67.5%) reported local AEs. Neither in IgG4-RD nor in HC, serious adverse reactions were observed. Among the patient’s cohort, 60% contracted SARS-CoV-2 infection, and 41.67% were on immunosuppressants at the time of the infection. One patient presented with severe COVID-19. No disease flares following vaccination or infection were reported.Conclusions. Results from our study indicate good adherence to the vaccination campaign against SARS-CoV-2 in patients with IgG4-RD and support a relatively good safety profile of this vaccine. Compared to controls, patients with IgG4-RD reported slightly more systemic AEs and fewer local AEs. A similar rate of COVID-19 development was observed between IgG4-RD patients and HC.
Keywords: IgG4-related disease; SARS-CoV-2; COVID-19; vaccination